Kompresi Data Text Menggunakan Metode â€œDuplicate Word Indexingâ€ - Primandari, Puteri Noraisya (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2018)
A data is often important so it should not be removed from data storage as it is used as an archive. The large number of new data archive data can slowly reduce free space and slow down the data transfer process. In this research, an approach is done to manage archive data by doing compression to minimize size. The results of this study were tested on some randomly books shows the number of data text size decrease of 19.46%. Keywords: data, archive, compression, text